2013
DOI: 10.1016/j.yrtph.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach for identifying and presenting mechanistic evidence in human health assessments

Abstract: Clear documentation of literature search and presentation methodologies can improve transparency in chemical hazard assessments. We sought to improve clarity for the scientific support for cancer mechanisms of action using a systematic approach to literature retrieval, selection, and presentation of studies. The general question was “What are the mechanisms by which a chemical may cause carcinogenicity in the target tissue?” Di(2-ethylhexyl)phthalate was used as a case study chemical with a complex database of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…We used the approach outlined in Kushman and Kraft et al (Kushman et al 2013) to construct this AOP. We used review papers (Barcellos-Hoff and Kleinberg 2013;Barcellos-Hoff and Mao 2016;Barcellos-Hoff and Nguyen 2009;Cadet et al 2017; Committee to Assess Health Risks from Exposure to Low Levels of Ionizing Radiation 2006; Hanahan and Weinberg 2011; Imaoka et al 2009;Kadhim et al 2013;Mukherjee et al 2014;Nguyen et al 2011a;Ravanat et al 2014;Ruhm et al 2016;Smith et al 2016;Sridharan et al 2015) to identify the mechanisms by which exposure to ionizing radiation may cause breast cancer.…”
Section: Methodsmentioning
confidence: 99%
“…We used the approach outlined in Kushman and Kraft et al (Kushman et al 2013) to construct this AOP. We used review papers (Barcellos-Hoff and Kleinberg 2013;Barcellos-Hoff and Mao 2016;Barcellos-Hoff and Nguyen 2009;Cadet et al 2017; Committee to Assess Health Risks from Exposure to Low Levels of Ionizing Radiation 2006; Hanahan and Weinberg 2011; Imaoka et al 2009;Kadhim et al 2013;Mukherjee et al 2014;Nguyen et al 2011a;Ravanat et al 2014;Ruhm et al 2016;Smith et al 2016;Sridharan et al 2015) to identify the mechanisms by which exposure to ionizing radiation may cause breast cancer.…”
Section: Methodsmentioning
confidence: 99%
“…The starting point for systematic evaluation is to conduct comprehensive searches of the peer-reviewed literature aimed at identifying mechanistic data ( Kushman et al 2013 ). The searches can be constructed to address a series of study questions in the PECO (population, exposure, comparator, and outcomes) framework ( Higgins and Green 2011 ) wherein end points associated with the key characteristics are identified.…”
Section: Using the Key Characteristics To Systematically Identify Ormentioning
confidence: 99%
“…However, mechanistic study databases present a challenge to systematic reviews in that the studies are typically both numerous and diverse, reporting on a multitude of end points and toxicity pathways. One recent example of a systematic approach searched for studies on end points relevant to nine cancer-related mechanistic categories in identifying and presenting mechanistic evidence on di(2-ethylhexyl) phthalate, a chemical with a complex database of > 3,000 research papers ( Kushman et al 2013 ). In this publication, the categories of mechanistic evidence were identified from a compendium of published reviews.…”
Section: Introductionmentioning
confidence: 99%
“…As an endocrine disruptor, DEHP is of great concern because of its toxic effects on the endocrine system, neural development, reproductive system, and multiple organs, including the liver, kidney, lung, and thyroid gland, which can result in cancer [13][14][15]. Regarding the effects of DEHP exposure to the liver, several studies have indicated that cholesterol metabolism disruption [2,3,16], Kupffer cell activation [17,18], hepatocyte apoptosis [13,19], and promotion of hepatic carcinoma [20] occur following exposure to DEHP. However, the mechanisms of long-term exposure to low-dose DEHP exposure in relation to hepatic stellate cell activation and liver fibrosis are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%